Multimedia for Fifth Year Medicine Professors and Students. Public Health Subject - Juan Rafael Zerquera Rodriguez; Sara Hernández Malpica; Hilda María Delgado Acosta; Margarita Romeu Escobar; María Lina Valdés Gómez; Pedro Hernández Sánchez; Jorge Cañella Granda; Juan Andrés Alemañy Co (Medisur)
Background: taking into consideration the potentialities of the use of information technologies, it is necessary for each teacher to develop methods of work where the use of the computer is a strong ally that permit improving the aids and teaching methods to win the quality of learning. Objective: elaborating a multimedia to support the fifth year Medicine teacher and students in Public Health subject. Methods: a multimedia was created departing from the software Creasoft 2, 1 created by a group of information-technology of Medical Sciences of Holguin. The foundations of the project for the introduction of documents, imagery and videos constructed in terms of the program of Public Health subject were created. Documentary revision and work in group of experts was accomplished in order to decide the contents of the software. Results: the multimedia works so that the students and professors can agree to the software and semesters validated for its utilization according to the program of the subject of study, exercises for themes are available, it is accessed to instructive, educational and counsellors videos of different contents, the literature is updated, counts with the health programs, actions of control of focus in transmissible diseases and other documents for fifth year Medicine professor and students. Conclusions: the created multimedia must contribute to elevate the quality of teaching because this means has been presented at the time and opportune conditions, adequately combined in terms of the fulfilment of the objectives.